ON THE IMPACT OF MONETARY POLICY ON THE ECONOMIC DEVELOPMENT OF RUSSIA - S. V. Laptev (Вестник университета)
The approaches of various authors to the assessment of the impact of monetary policy on the development of the economy have been considered. The main factors of positive and negative influence of interest rate monetary policy on economic development have been established. Features of influence of monetary policy on development of the developed and developing States have been revealed. It has been defined, that the strength of the influence of individual factors on the effectiveness of monetary policy in individual countries varies, and the appropriateness of using monetary policy to support economic growth is determined by the ratio of the total positive and total negative impact. Recommendations on the construction of monetary policy taking into account its positive and negative impact on the development of the economy have been given. They aim at a gradual transition to the use of monetary policy to support growth, to take into account all the factors of influence and the integrated use of all instruments of monetary and fiscal policy to stimulate growth, the achievement of other strategic objectives.